The use of Instagram for building Babysec’s digital communication and corporate reputation - Lopez-Villacrez, Alexandra (2024)
The growth of social networks and their influence have taken an important role in the purchase decision process of users. Therefore, it is relevant to understand and know what corporate communication strategies can generate in the digital reputation of the brand. For that reason, this study aims to analyze the perceptions of user mothers of the Babysec brand on the management of digital corporate communication through Instagram communities to generate corporate reputation. Its approach is qualitative, it is positioned in the interpretive paradigm and case design. Interviews were applied to six young mother’s consumers of the brand. From this, experiences were shared about the construction of a community on Instagram, immediate responses and attention by the brand, concern for accessible prices and products for different types of users, among others.